Management of Inclusion Education in Elementary Schools - Bayu Saputra Dullah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the management of inclusive Education in elementary schools. The method used is a literature review from previous articles analyzed to comply with the management of inclusive Education in elementary schools. Based on the results of the literature review, it is known that management is the process of planning, organizing, directing, and supervising the efforts of members of the organization and using other organizational resources to achieve the goals of the organization that have been set. Inclusive learning does not require children with special needs to familiarize themselves with the lives of reasonable citizens but can participate in the lives of citizens actively. In inclusive learning, learning is started as an effort to empower all abilities optimally and integrated so that all children can later contribute to the lives of residents for the benefit of living together. Departing from the above thoughts, in inclusive learning, it is not children who are required to adapt to the curriculum but the curriculum that must familiarize themselves with the needs of children to develop all their abilities. The consequence of such a principle is that adaptive learning programs are needed in Indonesia, known as individualized instructional programs, designed based on children's special needs.